Pengaruh Gaya Kepemimpinan, Komitmen Organisasi Dan Budaya Organisasi Terhadap Kinerja Pegawai Honorer Pada Dinas Perizinan Pelayanan Terpadu Satu Pintu Kabupaten Serdang Bedagai Tahun 2022-2023 - Anggita, Nadia Ayu; Siregar, Aisyah (Management And Business Progress, 2024)
Human resource management is the activity of planning, procuring, developing, maintaining and using human resources to achieve goals both individually and organizationally. The sample used in this research was 30 honorary employees who were in the District Investment and One-Stop Integrated Services Service. Serdang Bedagai. as a research sample. The analytical techniques used in this research are Instrument Testing, Classical Assumption Testing, Hypothesis Testing and Multiple Linear Regression Analysis. The results of this research show that hypothesis (1) shows that tcount (2.300) > ttable (1.703), likewise with a significance value of 0.007 < 0.05, it can be concluded that the first hypothesis is accepted, meaning that Leadership Style (X1) influences performance (Y) . hypothesis (2) it is known that tcount (8.012) > ttable (1.703), and the significance value is 0.00 < 0.05, so it can be concluded that the second hypothesis is accepted, meaning that the Organizational Commitment variable (X2) has an effect on the performance variable (Y). Hypothesis (3) shows that tcount (0.244) < ttable (1.703), and the significance value is 0.009 < 0.05, so it can be concluded that the third hypothesis is accepted, meaning that the Organizational Culture variable (X3) influences the performance variable (Y). In hypothesis (4), it is known that Fcount (22.939) > Ftable (2.975), and the significance value is 0.000 < 0.05, so it can be concluded that the fourth hypothesis is accepted, meaning Leadership Style (X1), Organizational Commitment (X2), Organizational Culture ( X3), have a joint (simultaneous) effect on the performance variable (Y).